2007
DOI: 10.1118/1.2742779
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a quality assurance program for computerized treatment planning systems

Abstract: In the present investigation, the necessary tests for implementing a quality assurance program for a commercial treatment planning system (TPS), recently installed at Sao Paulo University School of Medicine Clinicas Hospital-Brazil, was established and performed in accordance with the new IAEA publication TRS 430, and with AAPM Task Group 53. The tests recommended by those documents are classified mainly into acceptance, commissioning (dosimetric and nondosimetric), periodic quality assurance, and patient spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 16 publications
(20 reference statements)
0
7
0
1
Order By: Relevance
“…In this study, we commissioned Varian Eclipse TM v7.5 TPS in accordance with the procedure of the IAEA TRS-430 for clinical photon beams. The accuracy of the dosimetric calculation of Eclipse TM TPS v7.5.18 has been implemented and reported in detail by Camargo et al 21 It was reported that the most critical difference occurs for oblique incidence, oblique incidence off axis, shaped fields and off axis wedge. The QA of Eclipse TM TPS v7.3.10 has been reported in detail by Jamema et al 20 According to that report, it was determined that oblique incidence calculation does not show a variation outside the tolerance limits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we commissioned Varian Eclipse TM v7.5 TPS in accordance with the procedure of the IAEA TRS-430 for clinical photon beams. The accuracy of the dosimetric calculation of Eclipse TM TPS v7.5.18 has been implemented and reported in detail by Camargo et al 21 It was reported that the most critical difference occurs for oblique incidence, oblique incidence off axis, shaped fields and off axis wedge. The QA of Eclipse TM TPS v7.3.10 has been reported in detail by Jamema et al 20 According to that report, it was determined that oblique incidence calculation does not show a variation outside the tolerance limits.…”
Section: Discussionmentioning
confidence: 99%
“…A number of authors [20][21][22][23] have implemented dosimetric and non-dosimetric tests of QA procedure into TPS with the guidance of the IAEA TRS 430 report. These authors have reported that the most critical difference occurred for oblique incidence, oblique incidence-off axis, shaped fields and off axis-wedged.…”
Section: Qa Procedures In Tpsmentioning
confidence: 99%
“…The accuracy of the dosimetric calculation of Eclipse TM TPS v7.5.18 has been assessed and reported in detail by Camargo et al 7 . In this work, we focused both on dosimetric and non-dosimetric tests for commissioning and QA of Eclipse™ TPS.…”
Section: Discussionmentioning
confidence: 99%
“…6 Image reconstruction A. 7 2-D and 3-D display The purpose of the present study is to report the commissioning and QA of TPS using TRS 430 1 guidelines and to develop a QA program specific to our department. …”
Section: Introductionmentioning
confidence: 99%
“…Com o decorrer dos anos, o desenvolvimento da tecnologia proporcionou que se pudessem obter imagens por tomografia computarizada, melhorando, assim, a delimitação dos volumes do tratamento. Os sistemas de planejamento computadorizados incluem softwares e hardwares que possibilitam o uso de imagens anatômicas tridimensionais dos pacientes para realização do planejamento radioterápico, permitindo correções de heterogeneidades e cálculos de dose e distribuições de dose em três dimensões com maior rapidez e precisão(Podgorsak et al, 2005; IAEA, 2004) Camaro et al, 2007;Able et al, 2005;Mijnheer, 2004)…”
unclassified